(untitled) (Nuntius Antiquus, 2008)
The three odes written in greater asclepiad verse by Horace have a moralizing tone. This meter, with its marked diaereses after the sixth and tenth syllabes, favors exhortative and gnomicexpressions. In ode I 11, Horace explores asclepiad’s metrical characteristics selecting to each part of the verses words and expressions suitable to the rhythmic impression of the tripartite structure.Horace choses his words, rhythms, and images consciously and with great care.